FEATURES OF CEREBRAL HEMODYNAMICS AND MANIFESTATIONS OF HEPATIC ENCEPHALOPATHY IN CIRRHOSIS OF VIRAL ETIOLOGY AT DIFFERENT COMPENSATION STAGES WITH PRESERVED LEFT VENTRICULAR EJECTION FRACTION - V. E. Kulikov; T. A. Emelina; O. G. Kazakova; K. V. Nikolaevа; M. E. Hapman; M. A. Tonеeva (Рациональная фармакотерапия в кардиологии, 2017)
Aim. To study the features of the parameters of cerebral hemodynamics in extra and intracranial regions in viral hepatic cirrhosis A, B, C classes according to Child-Pugh with different serum levels of interleukin-2, interleukin-6 and tumor necrosis factor alpha and preserved left ventricular ejection fraction for improvement of diagnostics of stages of chronic hepatic encephalopathy.Material and methods. 107 patients with viral cirrhosis A, B, C classes according to Child-Pugh with different serum levels of interleukin-2, interleukin-6 and tumor necrosis factor alpha were included into the study. The parameters of hemodynamics in common carotid and middle cerebral arteries of the first order of both hemispheres as well as the parameters of echocardiography were studied in all patients. Evaluation of hepatic encephalopathy stages was carried out by the West-Haven symptoms scale and the Reitan test (Number Connection Test) according to the recommendations of the Working group of the XI-th World Gastroenterology Congress.Results. Reduction in the compensation of hepatic cirrhosis A and C classes was accompanied by a thickening of the intima-media complex in the common carotid arteries from 0.69±0.21 mm to 0.79±0.35 mm, respectively. The hemispheric asymmetry of the mean linear blood flow velocity tended to increase from 25.1±2.42% in cirrhosis A class to 39.5±7.94% in cirrhosis C class. The greatest disorders of the hemodynamics in the middle cerebral arteries were observed in hepatic cirrhosis C class due to changes in the linear blood flow velocity parameters, increase in the hemispheric asymmetry of the average linear flow rate up to 33.9±10.5%, reduction in resistance and pulsatility indices to 0.49±0.22 and 1.02±0.21, respectively.Conclusion. Chronic hepatic encephalopathy of all stages can occur in the presence of discirculatory disorders with the development of chronic cerebrovascular insufficiency in viral hepatic cirrhosis A, B, C classes with different serum levels of interleukin-2, interleukin-6 and tumor necrosis factor alpha and preserved systolic function of the left ventricle. The duration of the Number Connection Test more than 200 s, blood flow hemispheric asymmetry more than 40%, decrease in blood flow velocity parameters and vascular resistance indices in the middle cerebral artery below the reference values are associated with a poor prognosis of hepatic encephalopathy. The degrees of cognitive and discirculatory disorders are related with the stages of hepatic cirrhosis compensation. An increase in the degree of cognitive impairments (from ability to logical thinking and attention to disorientation in time and space) is observed in discirculatory disorders and decrease in the stage of cirrhosis compensation.